Conceptualizing the influences of locus of control, cognitive moral development and organizational culture on managers' socially responsible decisions - Darwin, Eka Noorul Baitie; Alias, Siti Noormi; Idris, Khairuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
This paper proposes a conceptual model about the influences of locus of control, cognitive moral development and organizational culture on managers’ socially responsible decisions. The discussions are based on an extensive review of past researches. From the literature reviewed, the three variables are identified to be predictors for managers’ socially responsible decisions. Conceptual framework on predictors affecting managers’ socially responsible decisions is developed and supported by the interactionist model of ethical decision making. Further research is suggested to test and validate the framework to provide empirical evidence. Upon model validation, the paper could offer practical interventions for HRD practitioners and assist organizations to identify factors affecting managers’ socially responsible decisions before planning CSR activities in organization.